Avaliação do impacto da realização de polissonografia no rastreio pré-operatório de síndrome da apneia obstrutiva do sono em pacientes submentidos à cirurgia bariátrica - Carvalho, Taíse Rosa de (2022)
Carvalho TR. Assessment of screening for obstructive sleep apnea with polysomnography in patients undergoing bariatric surgery. 79f. Dissertation (Master’s) – School of Medicine, Pontifical Catholic University of Rio Grande do Sul, Porto Alegre, 2022. Introduction: Obesity is increasing its incidence worldwide. Bariatric surgery is a therapeutic modality for obesity treatment that has excellent outcomes. To try to minimize the risks of bariatric surgery, a proper preoperative should be performed. There is a high prevalence of Obstructive Sleep Apnea Syndrome (OSA) associated with people with obesity, and different studies have found a relationship between the presence of OSA with postoperative pulmonary and cardiovascular events (<30 days) in different types of surgery. For this reason, different guidelines recommend screening for OSA in people undergoing bariatric surgery. However, polysomnography is an exam not widely available. Also, in the context of bariatric surgery, some studies diverged on the benefits of this screening. Objective: To assess the impact of OSA screening, using polysomnography, on cardiovascular and pulmonary complications in the postoperative period of bariatric surgery. Methods: This was a single-center retrospective cohort study, including 522 adults who underwent bariatric surgery between August 2010 and May 2019. Electronic medical records were accessed to obtain variables of interest. Screening for OSA was recorded as positive if the Apnea-Hypopnea Index was ≥5 events/hour in patients with no previous diagnosis of OSA. The primary outcome was the presence of cardiovascular and pulmonary complications in the 30-day postoperative period. Secondary outcomes include length of stay (days), need for an intensive care unit (ICU) after surgery, time to mechanical adaptation, and time to withdrawal from intensive care. Statistical analyzes were performed with χ2, Fisher's exact test, Student's t test, Mann-Whitney U test and Poisson regression. Results: We included 522 participants in this study, 326 underwent screening for OSA with polysomnography, and 196 did not undergo this screening. Baseline characteristics were similar between groups, except for the profile of some evaluated comorbidities (smoking, asthma, hypertension, heart failure), which were included in the logistic regression for correct analysis. There was no difference in cardiopulmonary events between the screening and non-screening groups (4.2% vs. 2.8%; P = 0.45). Polysomnographic screening did not reduce postoperative cardiovascular or pulmonary complications, RR = 1.73 (95% CI: 0.68–4.14). There was no difference between the groups regarding ICU admission, length of stay, and duration of mechanical ventilation. However, patients undergoing screening had a longer waiting time until the surgical procedure (average waiting time of 1,269 days in the screening group versus 827 days in the non-screening group). Conclusion: OSA screening did not change postoperative cardiovascular and pulmonary events in postoperative period. Also, screening is associated with longer waiting time for surgery. Therefore, OSA screening with polysomnography can be suppressed in the preoperative period of bariatric surgery. Indications for polysomnography should be made at the individual level and current preoperative guidelines should be reviewed.